Determining Technical and Resource-Use Efficiency in Rice Production in East Java - Wijaya, Amirullah; Rifin, Amzul; Hartoyo, Sri (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This study aimed to determine the technical and resource-use efficiency of East Java. The secondary data were used from the Paddy Cultivation Household Survey ST2013 handled by BPS-Statistics Indonesia. The data was cross-sectional and were derived from ST2013 in 2014. The stochastic frontier analysis analyzed the factors that drive rice output and quantified rice production's technical efficiency. In contrast, the marginal value product-marginal factor cost (MVP-MFC) approach was used to quantify resource-use efficiency in rice production. The SFA indicated that these factors positively affect rice output except for seed, fertilizer, labor, and land utilization. However, other factors were considered apart from the land size, such as exaggerated land and labor advantage in production and bad seed and fertilizer utilization. Technical efficiency varies considerably among rice farmers, ranging from 1 percent to 100 percent, with an average of 89 percent. Their technical inefficiency was influenced by their group membership, irrigation, credit, education level, and farmer age - external farm insect pests. The government and the private sector are involved in the programs through farmer groups. Keywords: agricultural production, allocative efficiency, resource-use efficiency, parametric frontier, ST2013, technical efficiency